Run silent, run deep - Gable, Clark, 1901-1960.; Lancaster, Burt, 1913-; Beach, Edward Latimer, 1918-; Wise, Robert; Jeffrey Productions, Inc.; MGM/UA Home Video (Firm) (Santa Monica, CA : MGM/UA Home Entertainment, 1958)
The realities of submarine warfare during World War II in the Pacific is centered around two submarine officers who are destined to clash with each other from the first moment they meet.
Based on the novel by Captain Edward L. Beach.
Originally produced as motion picture in 1958.
Director of photography, Russell Harlan ; music, Franz Waxman.
Clark Gable, Burt Lancaster, Jack Warden, Brad Dexter, Don Rickles, Nick Cravat.
Not rated.
DVD, Dolby surround stereo.
Keywords: Video recordings for the hearing impaired; World War, 1939-1945 -- Naval operations -- Submarine -- Drama; Feature films; War films; Submarine warfare -- Drama